“Estado del arte de la nanotecnología relacionado al medio ambiente y la sostenibilidad” - Farinango Aules, Diana Maritza (2024)
This research aimed to evaluate the current state of nanotechnology and its applications in promoting sustainable practices and environmental preservation. The focus of the study was to identify more effective and sustainable solutions to environmental challenges. The methodology used included a bibliographic review, the application of inductive and analytical methods, and specific data collection related to nanotechnology in the environmental and sustainability field, focusing on specialized documentary databases. The research results show that nanotechnology has great potential for developing production processes with lower environmental impact, greater sustainability, and lower energy consumption. Its effectiveness in the remediation of contaminated sites is particularly noteworthy, with a focus on water, air, and soil treatment. In the environmental industry, the most common nanotechnological materials are silver, silicon, titanium, zinc, graphene, and carbon, with titanium dioxide and carbon nanotubes being especially notable for their unique properties. In nanotechnology-assisted soil phytoremediation, nanoparticles such as zero-valent iron particles, titanium dioxide, carbon, and silicon are effective in soil remediation. In terms of air pollution, emphasis is placed on the use of nanoparticles and nanocomposites, particularly graphene oxide and other basic oxides, for the detection of common pollutants such as nitrogen dioxide, sulfur dioxide, and sulfur hydroxide. These findings highlight the strategic importance of nanotechnology in the development of more advanced and sustainable environmental solutions.